RECOMMENDED PROCEDURE FOR HIGHER EDUCATION PROGRAMS DESIGN - Evgeniya V. Karavaeva (Высшее образование в России, 2016)
The article proposes an algorithm for the development of educational programs of higher education in Russia, adapted from the “Tuning” methodology for the European educational standards. New possibilities for the development of modular educational programs are analyzed, taking into account new “framework” federal state educational standards (FSES 3+, and in future FSESB4). The article provides practical recommendations on the application of the competencies approach in the development and implementation of the educational programs of higher education.